The foundations of Clarence Finlayson´s metaphysical anthropology - Ochoa Disselkoen, Hugo (Estudios de Filosofía, 2011)
Clarence Finlayson, born in Valparaiso, was a Latin American thinker that taught in Medellín, Indiana, Mexico City and other cities of Latin America. This article aims at explaining the metaphysical foundations of his anthropology which, though rooted in the scholastic school of thought, are evidently influenced by the contemporaneous thought. Clarence Finlayson´s metaphysical conception is to re-understand the Aristotelic-Thomistic principles, thought from an articulation between being and nothing, as the basic poles of every becoming, which is distinctive to all compounded beings. Likewise, according to Finlayson, given that philosophy is grounded on a metaphysical intuition, since this intuition takes place in the experiential realization of the phenomenon of death in contrast with the desire of being absolutely, philosophy is, paradoxically, the essential discipline of mankind in an existential sense.